Genetic selection for resistance to Francisella orientalis shows significant selection response in Nile tilapia - Garcia, Baltasar F. [UNESP]; Restrepo-Arango, Jairo A. [UNESP]; Filho, Marcelo S. Silva [UNESP]; Sousa, Elielma L. [UNESP]; Agudelo, John F.G. [UNESP]; Mastrochirico-Filho, Vito A. [UNESP]; Manso, Shisley C.S. [UNESP]; Pereira, Carolina S. [UNESP]; Dias, Danielle C.; Leonardo, Antonio F.G.; Fonseca, Fernando S.; Tachibana, Leonardo; et al. (Elsevier, 2025)
Nile tilapia (Oreochromis niloticus) is one of the major aquaculture species, but its production is often challenged by emerging diseases, as francisellosis caused by Francisella orientalis. Selective breeding for disease resistance offers a sustainable alternative to prevent outbreaks in farming facilities. This study aimed to estimate the genetic parameters and evaluate the response to selection for resistance to F. orientalis in Nile tilapia. We conducted two sequential challenge tests across two generations (G0 and G1) to assess the heritability ( h 2 ) of resistance traits using pedigree information, including binary survival (BS) and time to death (TD). Additionally, six families in G1 were designated as controls, consisting of breeders with the lowest estimated breeding values (EBV). The realized response to selection (ΔGR) was estimated using the BS trait. The expected response to selection (ΔGE) was also estimated using the genetic parameters of the TD trait in the second challenge. Average TD results were lower in G1 than G0, 56.59 ± 17.27 and 73.70 ± 27.68 h, respectively. The h 2 estimates for G0, G1 and G0 + G1 were 0.399 ± 0.07, 0.282 ± 0.08 and 0.593 ± 0.07 for TD, and 0.454 ± 0.07, 0.266 ± 0.06 and 0.478 ± 0.06 for BS. The ΔGR at the family level were − 0.144 for G1 control, −0.0638 for G0, and 0.0122 for G1 resistance, indicating a positive effect of selection for resistance. The ΔGE showed potential genetic gains of 33 to 109 h in TD for the next generation depending on the selection intensity. The study found that resistance to F. orientalis in Nile tilapia has a significant additive genetic component and selective breeding can effectively improve disease resistance, with the potential for rapid genetic gains across generations.